Analytics of new psychoactive substances (NPS) - in search of optimal solutions - Magdalena Michalska; Monika Zajonz; Maciej Tadeusz Gawlik (Polish Pharmaceutical Society, 2020)
In recent years, new psychoactive substances (NPS) have become a popular alternative to traditional drugs. In the European Union Early Warning System of European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) the number of NPS increases each year. These substances known as legal highs or designer drugs are popular in particular among young people, mostly due to their price and availability. They are usually made in China and then sold in online stores. The variability of these substances and the lack of knowledge of their chemical structure and their metabolic changes pose a great challenge for toxicological analysis. Deaths caused by these drugs are underestimated due to their occurrence as a mixture of multiple drugs, further causing analytical problems. Difficulties in detecting NPS are also noticeable at diagnosis of intoxication, which carries the risk of misinterpretation and improper treatment. Rapid and inexpensive immunoassays used for drug detection have not yet been used in the identification of NPS. This is due to the dynamic changes on the drug market, which make it difficult to create appropriately sensitive and selective screening tests to identify an unknown substance. The production of specific antibodies takes a long time, often exceeding the duration of the presence of the substance in the illicit market. Scientists believe that mass spectrometry-based methods should be used to search for NPS in biological samples because they are sensitive and allow the determination of a specific compound with proper reliability. The use of high-resolution mass spectrometry (HRMS) in the context of screening may be a future strategy and alternative to classic drug tests. Nevertheless, the cost and time-consuming nature of this method currently exclude its use in routine diagnostics. An additional difficulty in carrying out identification is the presence of NPS in body fluids at low concentrations and frequently a short half-life time. In this article, we pay attention to the current analytical problems related to the detection of NPS.